Working Towards Collaborative Archaeology: Exploring Indigenous Perspectives on Archaeological Topics and Research Questions in Nain, Labrador - Piskor, Ashley (University of Waterloo, 2014)
Archaeology is one avenue that people use to understand the past. It is through these contemporary understandings of the past that cultural identities are created and maintained. Unfortunately, Indigenous perspectives have been marginalized in archaeology and are dominated by mainstream western views. Indigenous archaeologists are attempting to decolonize archaeology by incorporating Indigenous perspectives and by engaging in collaborative projects with Indigenous communities. A successful collaboration is when all parties are involved in all aspects of the project, especially research design and formulation of research goals. Based on interviews with local Aboriginal community members in Nain, Labrador, this study explores Aboriginal perspectives on archaeological research. It specifically examines the types of research topics and questions local community members have about the past and discusses how archaeologists can begin to answer these questions. This study is useful to archaeologists working in Labrador who wish to practice a more inclusive and community-engaged archaeology.